Room Function in the Roman Domus: A Study of Five Pompeian Houses - Romanowski, Ruth-Erika (My University, 1999)
Modem researchers struggle to ascertain spatial use in order to understand more fully the behavior of the inhabitants of the Roman house. As an artifact, the house has the potential to offer the most intimate glimpses of the interactions of the Roman family and Roman society. The artifactual, architectural, and decorative evidence which is preserved in Pompeian houses can provide insight into how the rooms and spaces of the Roman household functioned; room function itself can in tum tell more about the everyday lives of the people who inhabited the domus. But what is the value of the evidence found within the house? How much can the extant archaeological remains communicate to the modem researcher about the Roman family and how they used the spaces of the their homes? This thesis explores the potential of each type of evidence for evaluating room function and shows that only when all kinds of evidence are taken into account can the most informative picture of the Roman house emerge.
Keywords: Classics; Classics